Teaching comprehensive sexuality education in a traumatized society: recognizing teachers as sexual, reproductive, and mental health frontline workers - Macleod, Catriona Ida; du Plessis, Ulandi (Frontiers in Education, 2024)
Research on school-based sexuality education in South Africa, taught within Life Orientation (LO), has mainly focused on learners' responses, how teachers approach the subject, and the curriculum content. Critiques have included heteronormative biases, an emphasis on danger, disease and damage, a reinforcement of gendered binaries, and the lack of pleasure or wellbeing discourses. In contrast, our research focused on the unexpected moments teachers experience, i.e., the ethical, emotional or psychological challenges they encounter in their interactions with learners. We interviewed 49 teachers across a range of schools in three provinces. Data were analysed using narrative thematic analysis. Teachers' narratives referred to an alarming array of traumas and psychosocial problems experienced by learners, including sexual abuse, substance abuse, neglect, HIV diagnosis, unsafe abortion, witnessing murders, and attempted suicide. Teaching particular topics, they indicated, triggered learner distress, although, sometimes, distress was triggered by innocuous topics. Teachers felt insufficiently skilled to teach certain topics sensitively to promote the well-being of learners who experienced current or past trauma. They also felt ill-equipped to deal with learners reporting trauma or psychosocial problems to them. Strategies narrated included allowing learners to skip relevant classes, building trust, understanding learners' needs, being a learner's advocate, and drawing on learners' grounded expertise. Teachers spoke of experiencing burnout and secondary trauma themselves. We argue that LO teachers are, in effect, sexual, reproductive and mental health frontline workers. They need in-depth training in learner-centred and dialogical approaches to build trust within the classroom sensitively and in basic screening, containment, referral and lay counselling skills to assist distressed learners outside the class. A well-being approach to sexuality education requires providing LO teachers with ongoing support and consultation with peers and mental health professionals to avoid burnout and promote well-being. al., 2016) and how teachers approach the teaching of sexuality education (e.g., Francis &